From Leading to Guiding, Facilitating, and Inspiring: A Needed Shift for the 21st Century - C. June Maker (MDPI AG, 2021)
In the 21st-century context, problem solving, creativity, critical thinking, collaboration, and communication are the most valued skills in the workplace. Thus, those in positions often labeled as "leadership" need to make a valuable shift: to guiding, inspiring, and facilitating rather than directing. In this article, I review research on two styles of leadership, transformational and transactional, and relate this research to discussions of the same two types of giftedness. Research on the effectiveness of leaders at engendering creative problem solving has shown the transformational style to be more effective. Leaders are guides in the process rather than the content, facilitators of the gathering and exchange of information from varied sources, and role models as they exhibit effective problem-solving behaviors themselves. As role models, they inspire others to take risks, think innovatively, and collaborate with others. Examples of methods for identifying exceptionally talented leaders and behaviors to observe are provided. In addition, an evidence-based model for igniting, cultivating, extending, and strengthening exceptional talent in leadership is described.